888. In Vitro Forgiveness of INSTI-Containing Regimens at Drug Concentrations Simulating Variable Adherence. (4th December 2021) - Acosta, Rima K; Mulato, Andrew; D'Antoni, Michelle L; Yant, Stephen R; Cihlar, Tomas; White, Kirsten L
Abstract: Background: The integrase strand transfer inhibitor (INSTI)-based regimens bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF), dolutegravir (DTG)+FTC/TAF, DTG/lamivudine (3TC), and DTG/rilpivirine (RPV) are all used for treatment of HIV-infected patients. Here, relative time to in vitro viral breakthrough (VB) and resistance barrier using simulated human drug exposures at either full or suboptimal treatment adherence to each regimen were compared. Methods: Wild-type HIV-1 (IIIb)-infected MT-2 cells were exposed to the combinations of BIC+FTC+TAF, DTG+FTC+TAF, DTG+3TC, or DTG+RPV for up to 35 days or until VB. Fixed drug concentrations were the human plasma-free adjusted clinical trough concentrations (Cmin ) or fixed at simulated Cmin after missing 1 to 4 consecutive doses (Cmin -1 to -4), with many replicates. Drug resistance was studied by next-generation sequencing at ≥2% frequency. Results: At drug concentrations corresponding to full adherence and 1 missed dose (Cmin and Cmin -1), no VB occurred with any regimen (Table). At Cmin -2, only DTG+3TC had VB, with some emergent resistance to both drugs. At Cmin -3, all regimens had VB: by day 12, 100% of DTG+3TC wells had VB; for BIC+FTC+TAF, DTG+FTC+TAF, and DTG+RPV, < 15% of wells had VB which began after day 14. Emergent RT or IN resistance was seen for DTG+RPV and DTG+3TC but not for BIC+FTC+TAF or DTG+FTC+TAF. At Cmin -4, all DTG+3TC and DTG+FTC+TAF wells had VB by day 12, while DTG+RPV had 94% VB by day 25 and BIC+FTC+TAF had 50% VB by day 35. Emergent Cmin -4 drug resistance was seen for all regimens but at differing frequencies; DTG+RPV had the most wells with resistance. Cumulatively, emergent RT and/or IN resistance was found in 1.3% BIC+FTC+TAF, 2.5% DTG+FTC+TAF, 7.9% DTG+3TC, and 8.8% DTG+RPV cultures. Summary of Forgiveness and Barrier to Resistance of INSTI-Containing Regimens Conclusion: Regimen forgiveness and resistance barrier are important factors in long term treatment. These INSTI-based regimens had high in vitro forgiveness and resistance barriers with concentrations simulating high adherence. When multiple missed doses were simulated in vitro, BIC+FTC+TAF had the highest forgiveness and barrier to resistance. When compared to DTG+3TC and DTG+FTC+TAF, DTG+RPV had higher forgiveness but lower resistance barrier after several simulated missed doses. Disclosures: Rima K. Acosta, BS, Gilead Sciences, Inc. (Employee, Shareholder) Andrew Mulato, BS, MBA, Gilead Sciences, Inc. (Employee, Shareholder) Michelle L. D'Antoni, PhD, Gilead Sciences (Employee, Shareholder)Gilead Sciences, Inc (Employee, Shareholder) Stephen R. Yant, PhD, Gilead Sciences, Inc. (Employee, Shareholder) Tomas Cihlar, PhD, Gilead Sciences, Inc. (Employee, Shareholder) Kirsten L. White, PhD, Gilead Sciences, Inc (Employee, Shareholder)